MODEL PROJECT BASED LEARNING UNTUK MENINGKATKAN KETERAMPILAN MENULIS SEJARAH WANITA PADA MAHASISWA - Yeni Wijayanti (Jurnal Sejarah dan Budaya, 2017)
Pembelajaran sejarah yang menyenangkan dengan membuat kreasi mediasangat diperlukan agar motivasi siswa dalam belajar tinggi. Tulisan ini diharapkanmampu memberikan sumbangan pemikiran terhadap pengembangan ilmu kependidikanterutama yang menyangkut permasalahan yang ditemui dalam pembelajaran sejarahyang kontekstual, khususnya yang berkaitan dengan sejarah lokal, sehinggasiswa mendapatkan pemahaman yang lebih mendalam, pembelajaran yang menyenangkan,danprestasiyanglebihbaik.MetodeyangdigunakanadalahResearchandDevelopment(R&D).UntukmeningkatkanprestasibelajardankesadaransejarahsiswamakadikembangkanlahmediavideositusKerajaanGaluhyangtelahdilakukanujiinternal(validasi).Hasileksperimenmenunjukkanbahwamediavideo/audiovisualsitussejarahKerajaanGaluhefektifuntukmeningkatkankesadaransejarahsiswa. Joyfull teaching of history by making media creation is very important to increase student’s learning motivation. This paper is expected to contribute towardsthe development of educational science, concerning to the problems encountered inthe contextual learning of history, with regards to local history, therefore studentsgain a deeper understanding, fun learning, and better performance. This paper used aResearch and Development (R & D) method. To improve learning achievement andstudent’s historical awareness is developed by video media of Galuh Kingdom siteshas been validated. The experimental results showed that the media of video/audiovisual about historical sites of Galuh Kingdom is effective to increase the student’shistorical awareness